PENGARUH PEMBERIAN Trichoderma sp. DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN TANAMAN TOMAT (Solanum lycopersicum L.) - Nofita Maria Pandi'e; Abdonia W. Finmeta; Nur Aini Bunyani; Charisal M.A. Manu (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
Trichoderma sp. is a beneficial soil fungus known for its ability to stimulate plant growth and suppress disease-causing pathogens. This fungus also enhances nutrient availability by producing growth hormones and solubilize phosphate. This study was conducted in response to the increasing demand for tomatoes, while their productivity is often hampered by environmental conditions and pest attacks. The use of Trichoderma sp. offers an environmentally friendly alternative to chemical fertilizers and pesticides. It was carried out in Kayu Putih, Oebobo Subdistrict, Kupang City, from March to May 2025. The objective of this study was to determine the effect of different doses of Trichoderma sp. on the growth and yield of tomato plants (Solanum lycopersicum L.). The research employed a Completely Randomized Design (CRD). The design included five treatments: P0 (control), P1 (10 g), P2 (15 g), P3 (20 g), and P4 (25 g) per kg of planting medium, each replicated four times. Data were analyzed using ANOVA and the 5% LSD test. The results showed that P4 (25 g) produced the best outcomes across all parameters. Therefore, applying Trichoderma sp. at 25 g/kg of planting medium effectively enhances tomato plant growth.